Zastosowanie metody aktuarialnej w ubezpieczeniu społecznym - Szumlicz, Tadeusz (Use of Actuarial Method in Social Insurance, 2006)
Both in developed countries and transition economies the anticipation activities, as opposed to the intervention and creation ones, start to dominate the "new" social policy. One can also observe a tendency to use insurance method and insurance solutions in these social security systems which favour the anticipation actions.The insurance method - contrary to the endowment and protection methods used in social security - should represent a financing via contributions and, simultaneously, a specific entitlement to benefits derived from participation of the insured in the common risk pool. Thus, the terminology used in social policy for describing and assessing this method is important not only due to formal reasons and it clearly distinguishes between "social security" and "social insurance" (in singular) as a concrete social method and "social insurance arrangements" (in plural) as a set of social solutions.In this case, particularly essential is the social interpretation of insurance diagram (a description of consecutive terms: risk - premium - fortuitous event - loss - benefit) which explains social departures from the "classical" social insurance thinking and which also emphasises their causes and results.With regard to the deviations from the "classical" social insurance philosophy, the essential ones are those related to creating the risk pool (insurance compulsion), actuarial determination of contribution (different models for setting a premium) and insurance equivalency understood both as a fund equivalency (assets vs. liabilities) and as a compensation equivalency (benefits vs. contributions).An institutional solution to these issues in Poland is to be the Country Actuary. Naturally, some questions arise which concern its powers and real influence of his activities on the insurance-driven reform of social security. One should not omit here also the issue of quality evaluation of actuarial data used by such an institution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 109-129